MANAJEMEN SDM DALAM MENINGKATAKAN MUTU PELAYANAN DI LEMBAGA PENDIDIKAN MA TAHFIDZ QUR’AN AL ISLAMI PESANGGARAN TAHUN PEMBELAJARAN 2020/2021 - Lutfi Wakhid; Triyanto Triyanto (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Human Resource Management (HRM) is a form of acknowledgment of the importance of an organization (personnel) as a resource that can support the achievement of organizational goals, implementation of organizational functions and activities to ensure that they are used effectively and fairly for the benefit of the organization, individual, and society. The type of research used in this research is qualitative research, qualitative method is a social science research method that collects data in the form of words and actions or actions, and researchers do not calculate the qualitative data that has been obtained, and do not even calculate or analyze numbers. number. In this study, researchers in presenting the data through interviews, documentation, and observation. Data analysis uses data reduction, data presentation, drawing conclusions. This study aims to determine how the management of Human Resource Management (HRM) at MA Tahfidz Qur'an Al Islami Pesanggaran. To find out what the quality of service at MA Tahfidz Qur'an Al Islami Pesanggaran is like. To find out Human Resource Management (HRM) in improving the quality of services at MA Tahfidz Qur'an Al Islami Pesanggran. Based on the findings above that Human Resource Management (HRM) at MA Tahfidz Qur'an Al Islami Pesanggaran can be said to be good, this is proven in interviews with school principals, researchers also look at the condition of educators and employees at MA Tahfidz Qur'an institutions Al Islami can already be said to be responsible for carrying out their duties, and has also met the standardization of educational staff because almost all of the teachers at the MA Tahfidz Qur'an Al Islami institution have graduated S1. The situation of students at the MA Tahfidz Qur'an Al Islami institution, they are quite comfortable in the learning process in the classroom and outside the classroom, therefore even though this institution can be said to be a new institution, for the condition of students, researchers can conclude that it can be said to be good. The quality of service at the MA Tahfidz Qur'an Al Islami Pesanggaran institution can be said to be good although it still needs a lot of improvement. For the MA Tahfiz Qur'an Al Islami Pesanggaran school institution, the principal in particular should always try to pay attention and always provide motivation and enthusiasm for educators and employees so that they can work with enthusiasm and full of responsibility.